Association of asthma with coronary heart disease: A meta analysis of 11 trials. - Lida Wang; Shuyan Gao; Mingdong Yu; Zhixin Sheng; Wei Tan (PLoS ONE)
Purpose While the relationship of asthma and coronary heart disease (CHD) (a specific manifestation of cardiovascular disease) has not been described consistently, we tried to defined this relation and explore the influence of gender and asthma status (child- and adult-onset asthma) on this issue. Methods We searched published reports that described the relationship of asthma and CHD. Results Eleven trials were identified, covering 666,355 subjects. Asthma overall was significantly associated with CHD both for prospective trials (HR 1.34 [1.09,1.64], P = 0.005) and for retrospective trials(OR 1.29 [1.13,1.46], P = 0.001), when compared to individuals without asthma. Subgroup analysis split by gender indicated that females with asthma were significantly associated with CHD (HR 1.40 [1.20,1.62], P<0.001), but males with asthma were not significantly related with CHD (HR 1.19 [0.98,1.44], P = 0.07). For the four subgroups (Females with adult-onset asthma,males with adult-onset asthma,females with child-onset asthma,and males with child-onset asthma), pooled analysis of two trials indicated that only females with adult-onset asthma were significantly associated with CHD (HR 2.06 [1.32,3.19], P<0.001). Conclusions Our data indicated that asthma was associated with CHD, and the relationship between them seemed to derived mostly from females with adult-onset asthma. Considering the limits of our study, these findings should be taken with caution.